Childhood Abuse, Religious Involvement, and Lifetime Substance Use Disorders among Latinas Nationwide. (10th November 2018) - Ai, Amy L.; Lee, Jungup
ABSTRACT: Background : Childhood abuse is a major behavioral health concern and imposes lasting sequelae on mental and physical health, including lifetime substance use disorders (LT-SUD). Yet, gender-specific research examining this early trauma and substance use in Latina-Americans (Latinas) is scarce. No study has explored the relationship between collectivist cultural factors and LT-SUD in this largest minority-female subgroup of the United States' population. Objectives : Based on coping theory, this study investigated the association between childhood abuse, cultural factors, and LT-SUD among Latinas nationwide. Methods : Using the National Latino and Asian American Study we performed three-step logistic regressions to investigate LT-SUD for 1, 427 Latinas, following three preplanned steps: (1) childhood physical and sexual abuse (CPA and CSA) with LT-SUD; (2) known correlates as controls; and (3) cultural strength factors. Results : The prevalence rates of CPA and CSA were 28.0% and 18.4%, and that of LT-SUD was 4.8%. Religious attendance at a weekly level was negatively related to LT-SUD. Alongside English proficiency, discrimination, and social support, however, CPA and religious coping were positively associated with LT-SUD. Conclusion/Importance : Childhood physical abuse is an early risk factor for long-term substance use, viewed as a negative coping strategy. Religious attendance may have potential protection for Latinas. The victimization history may lead to coexisting positive (e.g., pursing social support, religious coping) and negative (e.g., SUD) coping behaviors within Latino communities.